Angle dependence of external and internal quantum efficiencies in bulk-heterojunction organic solar cells - Dennler, Gilles; Forberich, Karen; Scharber, Markus; Brabec, Christoph; Tomis, Igor; Hingerl, Kurt; Fromherz, Thomas (Journal of Applied Physics, 2007)
The realization of highly efficient organic solar cells requires the understanding and the optimization of the light path in the photoactive layer. We present in this article our approach to measure and model the optical properties of our bulk-heterojunction devices, and to control them in order to enhance the photovoltaic performances. We report our recent observations on the dependence of the external quantum efficiency (EQE) on the incidence angle of the light, and our results on the determination of internal quantum efficiency based on EQE measurement and optical modeling cross-checked by reflection measurements. We investigate poly(3-hexylthiophene): 1-(3-methoxy-carbonyl) propyl-1- phenyl [6,6] C61 based solar cells with two different thicknesses of the active layer (170 and 880 nm), and show that in the thin ones the absorption is enhanced for oblique incident radiation. © 2007 American Institute of Physics.